ANALISA FASILITAS TERMINAL DOMESTIK GUNA MENINGKATKAN LEVEL OF SERVICE BANDAR UDARA ZAINUDDIN ABDUL MADJID LOMBOK - Dimas Septiady Pratama Putra; Ahmad Musadek; Wiwid Suryono (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Lombok's Zainuddin Abdul Madjid International Airport is one of the airports located in Lombok, West Nusa Tenggara. Currently, there is a continuous increase in passengers at the domestic terminal of Zainuddin Abdul Madjid Airport. Airport facilities must be considered because they very influential on passenger satisfaction. The value of the level of service at an airport must be good and in accordance with the standards stipulated in the Minister of Transportation Regulation number PM 178 of 2015 concerning airport service standards. Lombok's Zainuddin Abdul Madjid International Airport has facilities for airport service users, such as passenger arrival and departure facilities, facilities provide comfort to passengers, facilities that provide added value to passengers, and terminal capacity that can accommodate passengers during peak hours. This research method uses descriptive quantitative method. Methods of data collection using the method of observation, documentation and literature study. The results show that Airport Terminal facilities are quite in accordance with the standards set in PM 178 Tahun 2015 but terminal facilities and capacity can still be increased to increase the value of the level of service.